External Fixation in the Emergency Department for Pilon and Unstable Ankle Fractures. Issue 12 (15th June 2019) - Shah, Kalpit N.; Johnson, Joey P.; O'Donnell, Seth W.; Gil, Joseph A.; Born, Christopher T.; Hayda, Roman A.
Abstract : Introduction: Pilon and unstable ankle fractures are often treated initially with an external fixator (ex-fix). Ex-fix application in the emergency department (ED) has been described but not compared with that placed in the operating room (OR). Methods: Retrospective, case-cohort study was performed at a level-1 trauma center. Using CPT codes, we identified patients who had surgical fixation of pilon or ankle fractures with an initial ex-fix application (in the ED or the OR). Postoperative outcomes and hospital logistical data were compared between the two groups. Results: Ninety-six patients met the inclusion criteria. The average age of patients was 47 years, and 54 (56%) of the patients were men. Thirty-three patients had the ex-fix placed in the OR, whereas 63 patients had the ex-fix placed in the ED. Postsurgical complications (prominent implant, nonunion, deep infection, deep vein thrombosis, loss of reduction) were seen in 6 of 33 patients in the ED ex-fix group and in 8 of 63 patients in the OR ex-fix group ( P = 0.51). Deep infections occurred in 2 of 33 patients in the OR ex-fix group and in 5 of 63 patients in the ED ex-fix group ( P = 0.71). Revision ex-fix for loss of reduction was performed in 4 of 33 patients in the OR ex-fix group and in 10 of 63 patients in the ED ex-fix group ( P = 0.59). Mean length of stay was 14 days for the OR ex-fix group and 13 days for the ED ex-fix group ( P = 0.35). Conclusion: No statistically significant differences were found in postsurgical complications (surgical or infectious) or ex-fix revision rates for the ED ex-fix group and the OR ex-fix group. Results indicate that uniplanar ex-fix may be safely applied in the ED. Level of Evidence: Level III, therapeutic